Business corruption in the Asia Pacific region: recapitulation and prospects. Issue 4 (8th August 2019) - Andrews, Tim G.; Rowley, Chris; Nimanandh, Khongphu; Buranapin, Siriwut
ABSTRACT: Corruption in its multiple guises remains one of the most discussed, yet under-researched, influences affecting business practice and organization management in Asia. Comprising conceptual and empirical approaches to explore both national and region-level examples, the research contained in this collection epitomize some of the many challenges involved. As a contribution, collectively the research go some way to advance our understanding of the causes, conditions and manifestations of corruption in Asian business, as well as to highlight the implications for practice in seeking to manage the consequences. However, further studies are required to consolidate, deepen and extend both how we perceive and engage with Asian business corruption. Opportunities for theoretical and practical advancement include revisiting the meaning(s) of the term 'corruption' itself, corruption as an informal institution, the moderating factors which connect corruption to process, performance and consequences and, finally, the methodological challenges involved in relevant empirical data collection and analysis.